2022
DOI: 10.1155/2022/5942109
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of Equipment for Anchor Cable with C-Shaped Tube Tension-Shear Test System

Abstract: Based on the phenomenon of serious tensile-shear failure of bolts and cables, domestic and foreign scholars’ research on the mechanical properties of bolts and cables has gradually changed from pure tensile to tensile-shear performance. To reduce the long-term bolt and cable breakage accidents in deep soft rock tunnels in coal mines, we independently developed a new type of support material—anchor cable with C-shaped tube and a corresponding tensile-shear test system. The system parameters are set through theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Their study results showed that the shear stress of anchors experienced an alternate change process from strong to weak, from weak to strong, and finally, from strong to weak. Tong et al [12] and Shan et al [13][14][15][16][17][18] proposed a combination of anchors and C-shaped canals for conducting double-shear tests. Their results proved that anchors and C-shaped canals could improve the transverse shear capacity of supporting materials during the shear process and strengthen the axial ultimate bearing capacity of anchors.…”
Section: Introductionmentioning
confidence: 99%
“…Their study results showed that the shear stress of anchors experienced an alternate change process from strong to weak, from weak to strong, and finally, from strong to weak. Tong et al [12] and Shan et al [13][14][15][16][17][18] proposed a combination of anchors and C-shaped canals for conducting double-shear tests. Their results proved that anchors and C-shaped canals could improve the transverse shear capacity of supporting materials during the shear process and strengthen the axial ultimate bearing capacity of anchors.…”
Section: Introductionmentioning
confidence: 99%